The politics of corruption, inequality, and the socially excluded - Santos Salas, Anna (Nursing philosophy, 2013)
In this article, the production of knowledge in the context of socially excluded people exposed to inequality, oppression, and exploitation is problematized. The analysis follows Enrique Dussel's philosophical exegesis of the politics of power and corruption and his vision of a critical transformation of the social political order. The argument is also informed by the work of critical educator Paulo Freire, who elucidates the conditions of oppression and marginalization and highlights the importance of conscientization to develop a critical awareness of these conditions. Hannah Arendt's work on the politics of understanding totalitarianism also assists in the elucidation of the machinery that operates behind oppression to sustain power and inequality. The article emphasizes the need to recognize the inequality of conditions that exists between the producer of knowledge and those who live through inequality and oppression in their lived corporality. A critical transformation of the process of production of knowledge is needed to both acknowledge the conditions that sustain this endeavour in the first place and avoid the corruption of knowledge. A work of conscientization is also necessary among knowledge producers to undertake a critical analysis of inequality that exposes the corruption of power. This analysis needs to examine and unmask the hidden mechanisms that perpetuate inequality and oppression and serve only the interests of a few. The abysmal gaps between the wealthy and the poor within and among countries bespeak a degree of human indifference that reflects a most serious and complex phenomenon that perverts something profoundly human in our societies.